Principles of Economics (Open textbook library., 2016)
This book is intended for a two-semester course in Economics taught out of the social sciences or business school. Principles of Economics aims to teach considerable range and depth of Economic concepts through an approachable style and methodology. The authors take a three-pronged approach to every chapter: The concept is covered with a “Heads Up” to ward off confusion, a real-world application for that concept, and a “You Try It” section to make sure students are staying on top of the concept.